Radial basis function neural network control for parallel spatial robot - Nguyen Hong Quang; Nguyen Van Quyen; Nguyen Nhu Hien (Universitas Ahmad Dahlan, 2020)
The derivation of motion equations of constrained spatial multibody system is an important problem of dynamics and control of parallel robots. The paper firstly presents an overview of the calculating the torque of the driving stages of the parallel robots using Kronecker product. The main content of this paper is to derive the inverse dynamics controllers based on the radial basis function (RBF) neural network control law for parallel robot manipulators. Finally, numerical simulation of the inverse dynamics controller for a 3-RRR delta robot manipulator is presented as an illustrative example.